Kinematics simulation for a new kind of underactuated robotic finger. (2nd October 2017) - Li, Xiali; Lan, Tianyi; Wu, Licheng
Abstract: In order to verify the design rationality and the properties of an Underactuated linkage Finger, we use Solidworks to simulate the grasp operation of the finger with different situations, which can be used to analyze the range of the grasping, the underactuated characteristic, the coherence of motion, and the mechanical property of the finger. The design of the proposed mechanism is based on spring systems that give the adaptive grasp capability of different objects. The results show the curve of angle, moment, and contact force. We can get the results that the finger can grasp the cylinders whose diameter can vary from 0.106 to 0.851 with respect to the finger length and can produce five times of hand grasping force by a small electromotor. The simulation can be used to analyze and verify the rationality and performance of the finger mechanism and the size design.